Avaliação de funcionalidade em atividades e participação de alunos com deficiência intelectual: elaboração de protocolo escolar - Miccas, Camila (2011)
A protocol based on the International Classification of Functioning, Disability and Health (ICF) was developed for the assessment of students with intellectual dis-ability, and its applicability was verified. The elaboration of such protocol involved different steps: an initial version of the protocol, a reviewed version attending the recommendations of the members of the Research Examination Committee, and the submission of this reviewed version to the judgment of three expert researchers. At the end of the process, only the component Activities and Participation of the ICF was elected to take part of the protocol here proposed. The applicability of this final version was verified in a restrictive pilot-study including teachers of the Fundamental Education I who had students with Down´s syndrome in their regular classrooms of the public education system of Barueri, SP, Brazil. The pilot-study with a control group (typically developing children) and children with Down syndrome, showed that the protocol evaluates the functionality and Participation in Activities, as appropriate. It was found by a questionnaire applied to teachers' receptiveness to the use of protocol in the school environment.